Establishment of cure kinetic model and study on reaction mechanism of resin-based thermal insulation coatings. (2017) - Wei, Li; Du, Andong; Fang, Yuan
This paper deals with the preparation of epoxy resin-based thermal insulation coatings using epoxy resin as matrix, in which a suitable amount of inorganic filler and fibre is added. The curing reaction rate versus time curves were obtained through analysing the isothermal curing process of the coating using the differential scanning calorimetry (DSC) method. The phenomenological method was used to study its curing kinetics, and the data fitting method was adopted to get some kinetic parameters of the n-order curing model, autocatalytic model and Kamal model. The dynamic DSC method and Fourier transform infrared spectroscopy were used to discuss its curing mechanism. Results show that the isothermal process of this coating conforms to the Kamal model, with a total reaction order m + n of 1.3-2.14. Both of the two curing reaction rate constants increase with the rise in temperature.